Low income and schizophrenia risk: A narrative review - Schneider, Miriam; Müller, Christian P.; Knies, Andrea K. (Behavioural Brain Research, 2022)
Despite decades of research, the precise etiology of schizophrenia is not fully understood. Ample evidence indicates that the disorder derives from a complex interplay of genetic and environmental factors during vulnerable stages of brain maturation. Among the plethora of risk factors investigated, stress, pre- and perinatal insults, and cannabis use have been repeatedly highlighted as crucial environmental risk factors for schizophrenia. Compelling findings from population-based longitudinal studies suggest low income as an additional risk factor for future schizophrenia diagnosis, but underlying mechanisms remain unclear. In this narrative review, we (1) summarize the literature in support of a relationship between low (parental) income and schizophrenia risk, and (2) explore the mediating role of chronic stress, pre- and perinatal factors, and cannabis use as established risk factors for schizophrenia. Our review describes how low income facilitates the occurrence and severity of these established risk factors and thus contributes to schizophrenia liability. The broadest influence of low income was identified for stress, as low income was found to be associated with exposure to a multitude of severe psychological and physiological stressors. This narrative review adds to the growing literature reporting a close relationship between income and mental health.
CRIS-Team Scopus Importer:2022-09-09
Keywords: Income; Mental illness; Risk factors; Schizophrenia; Stress